Autonomic Nervous System 2018
DOI: 10.5772/intechopen.77087
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System and Neurocardiac Physiopathology

Abstract: The autonomic nervous system regulates multiple physiological functions; how distinct neurons in peripheral autonomic and intrathoracic ganglia communicate remains to be established. Increasing focus is being paid to functionality of the neurocardiac axis and crosstalk between the intrinsic nervous system and diverse organ systems. Current findings indicate that progression of cardiovascular disease comprises peripheral and central aspects of the cardiac nervous system hierarchy. Indeed, autonomic neuronal dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 201 publications
(238 reference statements)
0
4
0
Order By: Relevance
“…Initially, we anticipated that the relevance in the AMI group would be highest, but our findings unexpectedly showed a high relevance in the UAP and chronic HF groups instead. The reason for this is that although norepinephrine is released from sympathetic nerves in AMI, it triggers sympathetic nerve remodeling to promote sympathetic hyperinnervation, therefore the direct influence of the changes in the glucose levels on autonomic nervous system was reduced, resulting in a weak correlation in patients with AMI ( 25 ). For this reason, the influence of changes in blood sugar values on autonomic nervous system was lower in the AMI group than in the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we anticipated that the relevance in the AMI group would be highest, but our findings unexpectedly showed a high relevance in the UAP and chronic HF groups instead. The reason for this is that although norepinephrine is released from sympathetic nerves in AMI, it triggers sympathetic nerve remodeling to promote sympathetic hyperinnervation, therefore the direct influence of the changes in the glucose levels on autonomic nervous system was reduced, resulting in a weak correlation in patients with AMI ( 25 ). For this reason, the influence of changes in blood sugar values on autonomic nervous system was lower in the AMI group than in the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The brain–heart axis is a well‐established and evolutionarily conserved circuit connecting frontal brain regions to the autonomic nervous system via limbic (i.e., amygdala), hypothalamic, and brainstem structures. Projections from the PFC extend to the insula and cingulate cortex, which project to both the amygdala and hypothalamus, which then project to the solitary nucleus and rostral ventrolateral medulla in the brainstem, regulating HR through sympathetic and parasympathetic projections to the sinoatrial node (the heart's endogenous pacemaker; Kingma et al, 2018). The solitary nucleus is also a critical hub for integrating bottom up (afferent) inputs from baroreceptors within the carotid bodies and vagal afferents.…”
Section: The Brain–heart Axismentioning
confidence: 99%
“…2). In a recent study in a rodent model of PAH, it was shown that VNS for several weeks attenuated pulmonary vascular remodeling, preserved RV function and improved survival (Yoshida et al 2018b); it accomplished that by chronically "re-setting" the balance between sympathetic and parasympathetic reflex circuits in the periphery and in the central nervous system (Kingma et al 2018).…”
Section: Targeting Autonomic Imbalancementioning
confidence: 99%